2021
DOI: 10.1186/s12903-021-01447-w
|View full text |Cite
|
Sign up to set email alerts
|

Perception of oral health and medical conditions as possible predictors of oral health status in visually impaired adolescents: a cross‐sectional study

Abstract: Background We aimed to assess oral health and oral hygiene status among visually impaired adolescents and also to evaluate the factors related to their oral health. Methods This was a cross-sectional study among 130 visually impaired adolescents in Tehran, Iran, in December 2018. Of three schools for visually impaired children in Tehran, children in the sixth to the tenth grade (aged 12–17 years) were included after obtaining their parents’ consent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
(45 reference statements)
0
2
0
1
Order By: Relevance
“…This difference between the results of the two studies can be due to different methodologies. Basir et al [15] showed significant effect of oral hygiene instruction on oral hygiene improvement of students. However, they provided traditional oral hygiene instruction using a dental model, which was different from our methodology.…”
Section: Discussionmentioning
confidence: 99%
“…This difference between the results of the two studies can be due to different methodologies. Basir et al [15] showed significant effect of oral hygiene instruction on oral hygiene improvement of students. However, they provided traditional oral hygiene instruction using a dental model, which was different from our methodology.…”
Section: Discussionmentioning
confidence: 99%
“…Perceived dental and gingival health were possible predictors for oral health status. 40 The in-depth interviews indicated that the respondents’ self-assessments were based on the number of remaining teeth in the mouth, the ability to chew, and missing front teeth.…”
Section: Discussionmentioning
confidence: 99%
“…14 siendo importante educar para la salud integral, por cuanto verse involucrado en problemas médicos puede hacer que haya más desconocimiento sobre la salud bucal. 15…”
Section: Discussionunclassified